Combined mini-TPP based on gas piston installation and steam turbine - P. A. Shchinnikov; N. V. Marasanov (Известия высших учебных заведений: Проблемы энергетики, 2017)
The paper proposes a technological scheme of the combined mini-TPP on the basis of gas-piston installation and a steam turbine, which may be required as part of the local or distributed power systems. It is shown that such a mini-TPP can be made in a modular layout, and its efficiency is not less than 50%, even without taking into account the optimization of thermodynamic, structural and circuit design and layout options. It is shown that the cost of production at a combined mini-TPP on ~8% lower than the installation of gas piston when working separately.